Evaluating the impact of fiscal and monetary policies on Indonesia’s macroeconomic stability and growth (2015-2019) - Muzayyanah, Muzayyanah; Triyana, Ega; Nawang Aura, Ken Agastya (Journal of Islamic Economics Management and Business (JIEMB), 2023)
Effective management of Indonesia’s macroeconomic variables –production, inflation, money supply, aggregate demand, and interest rates– is crucial for economic stability and growth. This study examines the fiscal and monetary policies implemented by the Indonesian government from 2015 to 2019 and assesses their impact on key macroeconomic variables. Utilizing a qualitative research approach and comprehensive literature review, the study analyzes the principles and implementation of these policies. Fiscal policies, including infrastructure development, social protection, and tax amnesty, significantly contributed to economic growth and reduced unemployment. Monetary policies, such as interest rate adjustments, open market operations, and reserve requirements, maintained inflation around 3% and improved liquidity. However, economic growth fluctuated, indicating the need for better policy coordination. The study highlights the importance of strategic fiscal and monetary policies in achieving macroeconomic stability and offers insights into optimizing these tools for addressing economic challenges and promoting long-term development in Indonesia.